CUSTOMER SATISFACTION AT R.W MONGISIDI GENERAL HOSPITAL SERVICE WITH IMPORTANCE PERFORMANCE ANALYSIS - Madundang, Novia; Pandowo, Merinda H. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Customer Satisfaction is the important thing in services quality, the hospital must give the best service to customer so the customer will be satisfied and wil be loyal. With many efforts, hospital must to make the patient feel comfortable with the services. The main objective is to analyze the importance and performance services at R.W Mongisidi General Hospital in Manado. The type of this research is descriptive quantitative methods. By using Impotance Performance Analysis (IPA) as analytical tool. In this research the samples taken are as much as 60 respondent (patient). The result of this research is (1) the level of importance, competence factor perceived to be important, for the level of performance is perceived to be low. (2) the level of importance, access factor is perceived to be important, for the level of performance, is to be low. (3) for the level of importance, courtesy factor is perceived to be important, for the level of performance access is to be high. (4) the level of importance, credibility factor perceived to be too important, for the level of performance, access is perceived to be high. So hospital management must keep the good work for the importance and performance to develop their hospital from better to be the best. Keywords: service quality, customer satisfaction, customer loyalty, performance.